The self-defense forces and postwar politics in Japan - Akihiro, Sado 1958-; Noda, Makito (Tokyo Japan Publishing Industry Foundation for Culture, 2017)
"In 1947, Japan eternally renounced war and the possession of armed forces with its constitution. How, then, did the Japan Self-Defense Forces (JSDF) survive, moreover, evolve over the ensuing 70 years into the prominent presence it is today? Sado Akihiro reviews the JSDF's history chiefly from the viewpoint of restrictions imposed on it by civil officials of the national bureaucracy, based on lessons gleaned from the arbitrary conduct of the military in pre-World War II days. He also explores the financial constraints placed on the JSDF in the form of a percentage of the GNP. This book traces the inside story of U.S.-Japan relations and Japan's defense policy. It attempts to shine a light on the true state of the JSDF in the midst of new challenges that put it at a crossroads, including post-9/11 international terrorism, North Korean nuclear development, and China's increased military presence in Asia"--Back cover.
Prologue : military of a nation that renounces war -- Beginning of the rearmament of Japan. Does establishment of the National Police Reserve constitute the rearmament of Japan? -- From National Safety Forces to Japan Self-Defense Forces -- The birth and growth of the JSDF. The defense agency and the JSDF -- The build up of defense capabilities and a series of defense build-up plans -- The Nakasone Plan and the argument for autonomous national defense -- Formulation of the National Defense Program guidelines -- During the second Cold War. Formulation of the guideline for Japan-U.S. defense cooperation What comprehensive security is -- Toward a stronger U.S.-Japan alliance -- The JSDF and the end of the Cold War. Lessons from the Gulf War -- Multilateral security cooperation vs. the U.S.-Japan security arrangements -- New threats and the new NDPG -- The JSDF at a turning point -- The transformation of Japan's Security Policy and the JSDF.
"Originally published in Japanese language as Sengo seiji to Jieitai by Yoshikawa Kobunkan Co., Ltd, in 2006. A completely new and original postscript was added by the author in 2017 to be included in the English version."--Title page verso.
Includes bibliographical references and index.
Text translated into English from Japanese.
Keywords: Japan -- Armed Forces -- History -- 20th century; Japan -- Defenses -- History -- 20th century